Hypotrichosis associated with capillary malformation–arteriovenous malformation syndrome. (11th December 2014) - Martín‐Santiago, A.; Knöpfel, N.; del Pozo, J.; Escalas, J.; Bartolomé, B.; Janer, V.; Pascual, M.; Nieto, C.; Hervás, J.A.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Capillary malformation–arteriovenous malformation (CM‐AVM) syndrome is characterized by multifocal small CMs and a risk for fast‐flow malformations. The disease is caused by mutations in the RASA1 gene, implicated in vascular development. What does this study add? Red punctate spots with pale halos are a frequent finding, as recently described. We report hypotrichosis associated with the CMs of CM‐AVM syndrome, suggesting that RASA1 gene mutations could be involved in hair follicle proliferation and the cell cycle.